2022
DOI: 10.3389/fimmu.2022.944286
|View full text |Cite
|
Sign up to set email alerts
|

Immune-related gene-based prognostic index for predicting survival and immunotherapy outcomes in colorectal carcinoma

Abstract: IntroductionColorectal cancer shows high incidence and mortality rates. Immune checkpoint blockade can be used to treat colorectal carcinoma (CRC); however, it shows limited effectiveness in most patients.MethodsTo identify patients who may benefit from immunotherapy using immune checkpoint inhibitors, we constructed an immune-related gene prognostic index (IRGPI) for predicting the efficacy of immunotherapy in patients with CRC. Transcriptome datasets and clinical information of patients with CRC were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Lin et al (31) found a strong correlation between the genes of the IRGPI and previously identified prognostic and clinically relevant indicators (OS, TNM stage, gender, age). In addition, Liang et al (32) illustrated that the interaction of immune-related genes based on IRGPI calculations may influence CRC formation and development. In contrast, more genes were included in our study with better predictive accuracy (the AUCs for 1-, 3-, and 5-year survival were 0.767, 0.800, 0.808 vs. 0.723, 0.724, 0.744).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lin et al (31) found a strong correlation between the genes of the IRGPI and previously identified prognostic and clinically relevant indicators (OS, TNM stage, gender, age). In addition, Liang et al (32) illustrated that the interaction of immune-related genes based on IRGPI calculations may influence CRC formation and development. In contrast, more genes were included in our study with better predictive accuracy (the AUCs for 1-, 3-, and 5-year survival were 0.767, 0.800, 0.808 vs. 0.723, 0.724, 0.744).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Liang et al. ( 32 ) illustrated that the interaction of immune-related genes based on IRGPI calculations may influence CRC formation and development. In contrast, more genes were included in our study with better predictive accuracy (the AUCs for 1-, 3-, and 5-year survival were 0.767, 0.800, 0.808 vs. 0.723, 0.724, 0.744).…”
Section: Discussionmentioning
confidence: 99%
“… multiple myeloma [ 57 ] miR-20a miR-20a downregulated MICA expression, reduced NK cell cytotoxicity, and was NKG2D dependent in cancer cells to promote tumour growth. colorectal cancer [ 60 , 61 ] miR-20a The regulation of MICA by miR-20a in ovarian cancer is similar to that in colorectal cancer. ovarian cancer [ 62 ] miR-17-92 cluster (miR-20a miR-20b miR-93 miR-106b) The regulation of MICA by miR-17-92 cluster in breast cancer is similar to that in ovarian and colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is among the most common fatal cancers worldwide [ 58 , 59 ]. The miR-20a expression level was significantly increased in CRC tissues [ 60 , 61 ]. Ovarian cancer (OC) is the most lethal malignancy in a woman’s reproductive system, and immunotherapy has a limited impact on treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Conception and design: ZL 1 and YD 3,4 . Administrative support: JZ 2 , RX 3,4 , JZ 5,6 and YJ 5,6 . Collection and assembly of data: ZL 1 .…”
mentioning
confidence: 99%